Below the parapet wall - beautifully carved miniature towers; Carving on the parapet wall - sequences from the epic Ramayana - Kishkinda kanda - Rama's meeting with Sugreeva - Brig. Ajai Singh (2021)
[ Image courtesy: Brig A.P. Singh - www.collectingmoments.in ] Parapet wall carving - Ramayana sequences from left to right. If you zoom into the parapet wall, you can see the sequences where Rama meets Sugreeva and Hanuman. The one image which is clearer is where Rama is shooting through seven trees with one arrow to prove his prowess to Sugreeva. The pact is, if Rama defeats Sugreeva's brother Vali, then Sugreeva would lend his army of monkeys to fight Ravana who has abducted Seeta.